Control of Oral Anticoagulation in Patients with the Antiphospholipid Syndrome – Influence of the Lupus Anticoagulant on International Normalized Ratio - Robert, A.; Querrec, Le A.; Delahousse, B.; Caron, C.; Houbouyan, L.; Boutière, B.; Horellou, M.H.; Reber, G.; Sié, P.; the Groupe «Méthodologie en Hémostase» du Groupe d’Etudes sur l’Hémostase et la Thrombose (Thrombosis and Haemostasis, 1998)
The recommended therapeutic range of International Normalized Ratio (INR) for oral anticoagulant treatment in patients with the antiphospholipid syndrome remains controversial. As a part of this controversy, it has been suggested that lupus anticoagulants (LA) could interfere with the determination of prothrombin time, thus questioning the validity of monitoring the treatment of these patients using INR. To clarify this point, we compared the values of INR obtained in the plasmas of two groups of patients, one without LA (n = 47), and the other with LA (n = 43). INR were determined using 8 different thromboplastin reagents on the same automated coagulation instrument. Chromogenic factor X, which is supposed to be insensitive to the presence of LA, was also measured. The results are the following: provided INR was calculated using calibrated reference plasmas, there was no significant difference between INR values obtained with the 8 reagents, both in the non-LA and in the LA groups (CV: 5.9 and 6.7%, respectively). Closer examination revealed that INR results obtained with one reagent (the recombinant thromboplastin Innovin) diverged from those of the 7 others, leading to an overestimation of INR, to a very large extent in some instances. However this effect was restricted to a subset of the patient population with LA (6 out of 43). Finally, the relationship between INR (average value obtained using the 8 reagents) and factor X was identical in non-LA and in LA patient groups. We conclude that, provided the reagents which display the LA interference are identified and excluded for this purpose, the INR system is valid for monitoring oral anticoagulant treatment in patients with LA.